Usability, quality, and factors influencing acceptance of a resilience app (JoyPopTM) among university students - Malik, Ishaq (My University, 2024)
Campus mental health (MH) services are struggling with increasing postsecondary student MH needs, and many students face barriers to MH care, which can have long-term negative impacts on their well-being. MH smartphone applications (apps) are one solution that can mitigate barriers to care by providing students with accessible MH support. The JoyPopTM app was designed to improve resilience and emotion regulation. While evidence suggests that using the JoyPopTM app is associated with better MH among students, factors influencing acceptance, usability, and quality must be examined to ensure a safe, engaging, and valuable user experience. The present study used the extended Unified Theory of Acceptance and Use of Technology (UTAUT2) to examine factors that influence the acceptance and use of the JoyPopTM app. The app's overall acceptance, usability, and quality were also evaluated. Participants were 183 postsecondary students attending a Canadian University who used the app for one week. Relationships posited by the UTAUT2 were tested using partial least squares structural equation modelling (PLS-SEM). Results showed that the UTAUT2 explained substantial variance in behavioural intention and app use. Performance expectancy, hedonic motivation, and facilitating conditions predicted behavioural intention, and behavioural intention and facilitating conditions predicted app use. Age moderated the association between facilitating conditions and behavioural intention. Experience moderated the relationship between performance expectancy, hedonic motivation, and social influence on behavioural intention. Participants rated the app's acceptance, quality, and usability highly. An exploratory analysis showed that quality and usability significantly predicted use, and personality traits showed unique associations with the UTAUT2 constructs. Findings provide insight into factors influencing the acceptance of the JoyPopTM app and support its utility as a helpful tool to support the increasing MH needs of postsecondary students. Findings also provide valuable insights for developers in evaluating and optimally designing MH apps.